DESAIN CLOUD KITCHEN BERORIENTASI KENYAMANAN - Ma'ruf, Yasmine Aminy; Rahman, Akbar (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
The Cloud Kitchens generally use buildings that are not designed to be used as intended. This has an impact on the occurrence of obstacles in use. Even though the kitchen plays an important role, it is necessary to design a good construction, equipment and supporting equipment.Cloud Kitchen is designed with the concept of Multi-Sensory Collective Kitchen which aims to make a kitchen that can support business owners in producing and developing their business. This design is oriented towards environmental comfort and can support users to use their five senses to produce good products.